Refugee Background Students Transitioning Into Higher Education Navigating Complex Spaces - Naidoo, Loshini (Springer Singapore, 2018)
This book is one of the first of its kind to examine the aspirations of refugee background students and accompanies them as they journey through the on-shore stage of settlement, enrolment and participation in the Australian education system. It begins with students' experiences of on-shore settlement, followed by the move into schooling and finally, the subsequent transition into Australian higher education. Transitioning into higher education is a challenge for many students, particularly for those from under-represented equity groups. For refugee background students, navigating in, through and out of higher education can be particularly complex and challenging. Drawing on rich case studies from longitudinal research into refugee youth and the academic and professional staff in schools and universities who support them, the book provides powerful and compelling narratives and insights into this journey. It untangles the complex nature of transition for students of refugee background in higher education, locating it within broader social trends of increasing social and cultural diversity, as well as government practices and policies concerning the educational resettlement of refugees.